Nanoalgosomes: Introducing extracellular vesicles produced by microalgae. Issue 6 (27th April 2021) - Adamo, Giorgia; Fierli, David; Romancino, Daniele P.; Picciotto, Sabrina; Barone, Maria E.; Aranyos, Anita; Božič, Darja; Morsbach, Svenja; Raccosta, Samuele; Stanly, Christopher; Paganini, Carolina; Gai, Meiyu; et al.
Abstract: Cellular, inter‐organismal and cross kingdom communication via extracellular vesicles (EVs) is intensively studied in basic science with high expectation for a large variety of bio‐technological applications. EVs intrinsically possess many attributes of a drug delivery vehicle. Beyond the implications for basic cell biology, academic and industrial interests in EVs have increased in the last few years. Microalgae constitute sustainable and renewable sources of bioactive compounds with a range of sectoral applications, including the formulation of health supplements, cosmetic products and food ingredients. Here we describe a newly discovered subtype of EVs derived from microalgae, which we named nanoalgosomes. We isolated these extracellular nano‐objects from cultures of microalgal strains, including the marine photosynthetic chlorophyte Tetraselmis chuii, using differential ultracentrifugation or tangential flow fractionation and focusing on the nanosized small EVs (sEVs). We explore different biochemical and physical properties and we show that nanoalgosomes are efficiently taken up by mammalian cell lines, confirming the cross kingdom communication potential of EVs. This is the first detailed description of such membranous nanovesicles from microalgae. With respect to EVs isolated from other organisms, nanoalgosomes present several advantages in that microalgae are a renewable and sustainable natural source, which could easily be scalable in terms of nanoalgosome production.